2017
DOI: 10.1038/srep44546
|View full text |Cite
|
Sign up to set email alerts
|

Novel transcriptome assembly and comparative toxicity pathway analysis in mahi-mahi (Coryphaena hippurus) embryos and larvae exposed to Deepwater Horizon oil

Abstract: The impacts of Deepwater Horizon (DWH) oil on morphology and function during embryonic development have been documented for a number of fish species, including the economically and ecologically important pelagic species, mahi-mahi (Coryphaena hippurus). However, further investigations on molecular events and pathways responsible for developmental toxicity have been largely restricted due to the limited molecular data available for this species. We sought to establish the de novo transcriptomic database from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 85 publications
(99 reference statements)
4
26
0
Order By: Relevance
“…The mahi mahi study noted activation of these same three pathways in both life stage transitions 19 . Interestingly, magnitude and directionality of immune-related transcriptional responses appear to depend on length of oil exposure and type of oil: most immune-related pathways were activated at 96 hours of exposure to slick oil in mahi mahi, but were mostly unaffected at 96 hours of exposure to source oil 20 . At 48 hours of exposure to source of slick oil (the same amount of time as our exposure duration), most immune pathways were suppressed or unchanged in mahi mahi, and at 24 hours of exposure to source or slick oil, no immune pathways were altered 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mahi mahi study noted activation of these same three pathways in both life stage transitions 19 . Interestingly, magnitude and directionality of immune-related transcriptional responses appear to depend on length of oil exposure and type of oil: most immune-related pathways were activated at 96 hours of exposure to slick oil in mahi mahi, but were mostly unaffected at 96 hours of exposure to source oil 20 . At 48 hours of exposure to source of slick oil (the same amount of time as our exposure duration), most immune pathways were suppressed or unchanged in mahi mahi, and at 24 hours of exposure to source or slick oil, no immune pathways were altered 20 .…”
Section: Discussionmentioning
confidence: 99%
“…We then performed RNAseq and bioinformatic analyses to determine differentially expressed transcripts and pathways between treatment groups and age stages, with a specific focus on immune-related genes and pathways. Previous research in developing fish has found that exposure to oil does significantly impact some immune-related pathways [19][20][21] . Therefore, we wanted to examine how the effects of these stressors change transcriptional patterns as the developing fish undergo two significant transitions: between the embryonic and post-hatch life stages, and between the post-hatch and post-larval life stages.…”
mentioning
confidence: 99%
“…Recently, a study linked oil-induced changes in lipid composition and dynamics to reduced growth and survival in polar cod (Boreogadus saida) (Laurel et al, 2019). Consistently, impacts on lipid metabolism pathways have been reported in several RNAseq studies (Sørhus et al, 2017;Xu et al, 2017). Several gene expression studies have started to unravel initiating events and key events of adverse outcome pathways of crude oil (Laurel et al, 2019;Lie et al, 2019;McGruer et al, 2019;Sørhus et al, 2017), but there are still knowledge gaps in understanding the underlying mechanisms of crude oil toxicity.…”
Section: Introductionmentioning
confidence: 88%
“…A circulation-and time-independent expression of bmp10 suggests a direct effect of crude oil on calcium homeostasis. Several signaling pathways linked to cardiac development and proliferation are impacted by the complexity of crude oil exposure, including calciumregulated pathways (Sørhus et al, 2017;Xu et al, 2017), AhR (Yin et al, 2008) and retinoic acid (Lie et al, 2019)-dependent pathways. Disruption of intracellular calcium levels has been shown to reduce cardiomyocyte proliferation leading to smaller ventricles (Ebert et al, 2005;Rottbauer et al, 2001), suggesting that ventricular proliferation is calcium controlled.…”
Section: Cardiac Morphological Defectsmentioning
confidence: 99%
“…Xu et al . () analysed genes responsible for deep‐water horizon oil toxicity in mahi‐mahi ( Coryphaena hippurus ). This study described the genes causing toxic effect such as liver proliferation, cholesterol biosynthesis, cardiac hypertrophy, and renal necrosis/apoptosis.…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 99%